ELEMENTARY MATHEMATICS IN THE COURSE " MODULAR INEQUALITIES SOLUTION ” TOPIC OF TEACHING GOALS - Jumakulov X. Q.; Obidjonova M. (Galaxy International Interdisciplinary Research Journal, 2023)
Inequalities department of mathematics main meaningful from directions is one Inequalities function concept with directly depends has been issues both in learning and other many It is also used in concepts .